Multi-User I Intrference Mitigation in TR UWB Receiver via Mid-point Impulse Correlation Technique - Natiq Abdullah Ali (Journal of Madenat Alelem University College, 2014)
Impulse radio-ultra wideband (IR-UWB) is a wireless technology system that offers a high data rate within a short range. Therefore, IR-UWB system is regarded as an excellent physical layer solution to the multi-piconet Wireless Personal Area Network (WPAN) applications. In spite of all the advantages of IR-UWB, there are several fundamental and practical challenges that need to be carefully addressed. The big and most important one among these challenges is the interference. In this paper, to largely suppress the Multi-User Interference (MUI), a very simple novel Midpoint Impulse Correlation (MIC) technique is proposed instead of the conventional correlation. The proposed technique is programmed using Matlab R2008b software and tested in various suggested scenarios close to the realistic multi-piconet WPAN environments using the dense multipath indoor IEEE 802.15.3a CM2. The performance results for the proposed technique exhibited lower SERs values as compared with the conventional correlation.